2021
DOI: 10.1080/21645515.2021.1935170
|View full text |Cite
|
Sign up to set email alerts
|

Improved post-marketing safety surveillance of quadrivalent inactivated influenza vaccine in Mexico using a computerized, SMS-based follow-up system

Abstract: Quadrivalent influenza vaccines (QIVs) are designed to prevent influenza disease caused by two influenza A viruses (H1N1 and H3N2) and both influenza B lineages. Risk-monitoring of QIVs to identify adverse events (AEs) is necessary as influenza vaccines are reformulated each year. We developed a new active surveillance system (Sistema de Control de Vacunación; SICOVA) to improve pharmacovigilance in Mexico. Participants (N = 2013) aged 0 − 96 years from nine sites across three influenza seasons (n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Although the electronic ADR completion rate was lower than traditional active studies, 20 or web‐based intensive monitoring, 21 the completion rate in this study falls within the range observed in other surveillance studies using an e‐PRO system. 22 , 23 , 24 Therefore, e‐PRO systems can still be used to collect safety information, for example, to limit the burden of work for sites or to monitor safety when a site visit is not possible, for example, during COVID‐19 lockdowns.…”
Section: Discussionmentioning
confidence: 99%
“…Although the electronic ADR completion rate was lower than traditional active studies, 20 or web‐based intensive monitoring, 21 the completion rate in this study falls within the range observed in other surveillance studies using an e‐PRO system. 22 , 23 , 24 Therefore, e‐PRO systems can still be used to collect safety information, for example, to limit the burden of work for sites or to monitor safety when a site visit is not possible, for example, during COVID‐19 lockdowns.…”
Section: Discussionmentioning
confidence: 99%